ANALYSIS OF THE IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 58 OF 2023 ON THE WITHHOLDING OF ARTICLE 21 INCOME TAX FOR PERMANENT EMPLOYEES AT PT XYZ - Cahyo, Aqil Dwi; Karunia, Asaprima Putra; Persadha, Yoga; Suranta, Sri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The shift in the calculation system for withholding Income Tax Article 21 from a progressive rate to the Average Effective Rate (TER) scheme offers administrative ease for taxpayers in fulfilling their tax withholdings. However, there are differences in tax burdens among permanent employees of PT XYZ falling into various TER groups (A, B, and C) based on their Non-Taxable Income (PTKP) status. These differences become more significant when gross income increases, such as when religious holiday bonuses are provided, causing some employees previously not subject to withholding tax to become taxable. The total amount of Income Tax Article 21 withheld under the TER scheme tends to be higher than that calculated using the progressive rate. These findings indicate that although TER simplifies administrative procedures, the classification of TER groups and fluctuations in gross income are crucial factors in determining the tax burden borne by each employee.